An introduction to security in a CSM 1.3 for AIX 5L environment - Lascu, Octavian (IBM redbooks., 2002)
This IBM Redbooks publication contains information about the first official release of the new clustering software IBM Cluster Systems Management (CSM) on AIX 5L Version 5.2. Features include base cluster configuration and management, Resource Monitoring and Control (RMC), subsystem access control list setup for shipped CSM resource managers, hardware control, configuration file management, distributed command execution, and a distributed GUI based on the AIX WebSM infrastructure. Included in this release of CSM is a complete set of base security functions based on IBM host-based authentication (HBA) and offered through an abstraction layer in the CSM software. CSM automatically configures HBA for use by the cluster services and establishes secure cluster communications for the shipped CSM resource managers. The first part of this publication is conceptual and includes an introduction to security for CSM 1.3 for AIX 5L, security concepts and components, and CSM security infrastructure. Next, practical security considerations are provided. Topics, such as network considerations, security in an heterogeneous environment, and security considerations for hardware control, are discussed. The last part of this publication details secure remote command execution, as well as security administration. Among the topics covered are remote command execution software, OpenSSH installation, and administration of RMC.